The Effect of Work Motivation and Discipline on Employee Performance: Study at a Consumer Goods Distributor Company in Bandung - Prasetyawan, Rifky Adjie; Hadian, Dedi; Machmud, Senen; Manik, Ester (Acman: Accounting and Management Journal, 2023)
The COVID-19 pandemic has significantly impacted employees by necessitating the adoption of remote work arrangements, resulting in a decline in their performance, effectiveness, and efficiency. The employees of a distributor company in Bandung witnessed a decrease in their performance after the company transitioned to a Work From Office arrangement. The observation of the attendance recapitulation for 2021 reveals that 179 employees were absent due to various reasons such as illness, leave, or unauthorized absence. The aforementioned numerical values undeniably impact the productivity of every individual employed at the distributor organization. Employee discipline is crucial in fostering motivation and enhancing performance in subsequent periods. The study utilized a quantitative research methodology characterized by a descriptive and verificative design. The study utilized a sample size of 50 participants employed at a distributor company in Bandung. The participants were selected through the implementation of stratified random sampling. The primary data for this study gather via questionnaires administered directly to employees of the distributor company. According to the study results, all of the statement items demonstrated validity, as indicated by values exceeding 0.30. Additionally, these items deem reliable, as evidenced by values surpassing 0.60. The motivation variable achieved a score of 0.979, the discipline variable attained a score of 0.975, and the employee performance variable obtained a score of 0.983. The t-test results showed that the calculated t-value was 4.218 with a significant level of 0.000 and 3.902 with a significant level of 0.000, exceeding the t-table value of 2.001. The R Square value indicated that 78.9% of employee performance is influenced by motivation and discipline, while the remaining 21.1% represented other unexplored factors. Furthermore, motivation had a total effect of 41.17%, while discipline had a greater influence with a total effect of 37.71%. The distributor company in Bandung should prioritize motivation by continuously providing incentives that enhance employee performance and implementing discipline regulations agreed upon by the company and employees. It is anticipated that implementing these measures will result in enhanced employee performance within the distributor company located in Bandung.